Larangan Keluar Rumah Pada Malam Satu Suro Prespektif Pendidikan Aqidah Ahlussunnah - Wiwik Zuliana Sukmawati; Darnoto Darnoto (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
This study discusses the tradition of prohibiting people from leaving their homes on the night of Satu Suro from the perspective of Ahlussunnah Wal Jama’ah creed education in Sekuro Village, Mlonggo District, Jepara Regency. The research aims to examine the community’s understanding of the Satu Suro tradition and the Islamic creed’s perspective toward such beliefs. This study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The informants consisted of religious leaders, community leaders, village elders, and local residents who still practice the tradition. The results show that the prohibition of leaving the house on the night of Satu Suro is understood by the community as a form of caution and respect for ancestral traditions. Older generations tend to believe in the sacredness of the tradition more strongly, while younger generations view it mainly as a cultural heritage that should be respected without being believed absolutely. From the perspective of Ahlussunnah Wal Jama’ah creed, the belief that the night of Satu Suro can absolutely bring misfortune contradicts the principle of monotheism (tauhid). However, the tradition may still be preserved as part of local culture as long as it does not contain elements of shirk or superstition.